1988
DOI: 10.1101/gad.2.10.1284
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a histone H1-like protein is restricted to early Xenopus development.

Abstract: Genes whose expression is restricted to oogenesis and early development may have important functions in these processes. Northern analysis showed that Xenopus B4 mRNA is expressed in oogenesis and embryogenesis through to the neurula stage. Immunocytochemistry with anti-B4 antibodies showed that B4 protein is only detectable in preneurula stages; it is localized to nuclei and is associated with metaphase chromosomes. Immunoblotting revealed approximately constant levels of B4 protein per embryo for the first 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 48 publications
1
123
0
3
Order By: Relevance
“…The two cDNAs were cloned into pBS-RNT3, transcribed, and translated in vitro in the presence of [ 35 S]methionine. cDNA of B4, the linker histone subtype specific to Xenopus early embryos (13), was isolated by PCR. Full-length cDNAs encoding p60 xNAP-1 and B4 were cloned into the pTrcHis plasmid vector (Invitrogen) and transformed into Escherichia coli BL21.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two cDNAs were cloned into pBS-RNT3, transcribed, and translated in vitro in the presence of [ 35 S]methionine. cDNA of B4, the linker histone subtype specific to Xenopus early embryos (13), was isolated by PCR. Full-length cDNAs encoding p60 xNAP-1 and B4 were cloned into the pTrcHis plasmid vector (Invitrogen) and transformed into Escherichia coli BL21.…”
Section: Methodsmentioning
confidence: 99%
“…In Xenopus eggs, the core histones H2A-H2B and H3-H4 stored in the cytoplasm are associated with histone chaperones nucleoplasmin and N1͞N2, respectively (11,12). To investigate whether B4, the linker histone of Xenopus eggs (13)(14)(15), is found complexed to other proteins, egg extract was fractionated by gel filtration (Superose 12), and fractions were probed with Abs to B4. The result showed that B4 contained in egg extract was eluted considerably faster from the column than purified B4 in physiological buffer, whereas it was eluted at the same position as purified B4 in high-salt buffer containing 0.5 M KCl (Fig.…”
Section: Incorporation Of Linker Histones Into Dinucleosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…TFIIIA activation of transcription is therefore more vigorous within the histone Hi-deficient chromatin later in development (15 hr postfertilization) when histone H 1 would have normally substantially replaced histone B4 in chromatin (Dimitrov et al 1993). The cleavage linker histone B4 is much more acidic in the carboxy-terminal tail than histone H1 (Smith et al 1988;Dimitrov et al 1993); hence, like phosphorylated histone H1, it might be expected to have a weaker interaction with DNA (Jerzmanowski and Cole 1990). Thus, B4 may not compete effectively with transcription factors for association with the oocyte 5S rRNA genes.…”
Section: Gene Expression In Hi-deficient Embryosmentioning
confidence: 99%
“…In the sea urchin (Strongylocentrotus), there are distinct sperm, cleavage, and adult linker histones (Newrock et al 1977;Levy et al 1982;Knowles et al 1987;Lai and Childs 1988). In Xenopus laevis during embryogenesis, there is a transition from a cleavage (B4) to an adult (H1), to a specialized linker histone found predominantly in terminally differentiated, nondividing cells (HI°), (Perry et al 1985;Smith et al 1988;Dimitrov et al 1993;Khochbin and Wolffe 1993). The structural and functional significance of these transitions has not been determined.…”
mentioning
confidence: 99%